2013
DOI: 10.1038/sj.bdj.2013.686
|View full text |Cite
|
Sign up to set email alerts
|

A review of the success and failure characteristics of resin-bonded bridges

Abstract: All types of resin-bonded bridges provide an effective short- to medium-term option, with all-ceramic performing least well and having the least favourable mode of failure. The methods of failures were different for different bridges with metal frameworks performing the best over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 61 publications
2
51
0
6
Order By: Relevance
“…The failures of RBFPDs are usually less catastrophic than failures with conventional FPDs . The main advantages of RBFPDs are conservation of tooth structure, reduction of pulpal morbidity, and use of supragingival margins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The failures of RBFPDs are usually less catastrophic than failures with conventional FPDs . The main advantages of RBFPDs are conservation of tooth structure, reduction of pulpal morbidity, and use of supragingival margins.…”
Section: Introductionmentioning
confidence: 99%
“…A recent update by the same group published in 2017 estimated a 91.4% survival of RBFPDs after 5 years and 82.9% after 10 years . Miettinen et al reported an estimated annual failure rate of 4.6% for metal frameworks, 4.1% for FRC frameworks, and 11.7% for all ceramic RBFPDs . Chen et al in his review found that all‐ceramic RBFPDs had an estimated 5 year survival rate of 91.2% …”
Section: Introductionmentioning
confidence: 99%
“…The minimum connector dimensions, which vary according to the types of ceramics used, need to be respected to ensure sufficient rigidity and strength [16]. Although all ceramic resin bonded prostheses offer superior aesthetic potential compared to their metal base counterparts, the brittle nature of the ceramics does not permit intact removal for reuse whereas removal by mechanical tapping and recementation is possible with metal-based prostheses.…”
Section: Laboratory Made Resin Bonded Fixed Partial Prosthesismentioning
confidence: 99%
“…CAD/CAM fabrication can be a cost-effective alternative to a laboratory-manufactured, long-term provisional prosthesis. Figures demonstrated the utilization of CAD/CAM technology for the construction of full arch zirconia, implant supported fixed maxillary and mandibular prostheses [13][14][15][16]. Figure 5a showed the intra-oral teeth set up try-in of the full arch implant supported prostheses.…”
Section: Cad/cam Provisional Prosthesesmentioning
confidence: 99%
“…An analysis of published data on resin bonded bridges revealed that all-ceramic frameworks had the highest annual failure rates at 12% compared to 5% for metal-framed and 4% for fibre-reinforced. Given that all-ceramic bridges performed least well and the most frequent complications of all-ceramic bridges was fracture of the framework (57%) [2].…”
Section: Introductionmentioning
confidence: 99%